2023
DOI: 10.1111/jan.15519
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of racism and perinatal depression: Findings from the pregnancy risk assessment monitoring system, 2018

Abstract: Aim:To estimate the association between feeling upset by experiences of racism and self-reported depression during pregnancy among non-Hispanic Black women using a large population-based sample from the United States. Design:We conducted a secondary analysis of nationally representative crosssectional survey data with retrospective measures. Methods: Analysis of Phase 8 (2018) data from the Pregnancy Risk AssessmentMonitoring System survey included 7328 non-Hispanic Black respondents with a recent live birth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Populations marginalized by racism and socioeconomic disadvantage experience significant health inequities in the prevalence, screening, treatment, and outcomes related to perinatal mental health conditions (7,102). Analysis of PRAMS (Pregnancy Risk Assessment Monitoring System) phase 8 2018 data, including 7,328 non-Hispanic Black respondents with live births from 11 states and New York City and controlling for potential confounders, showed that respondents who felt upset due to experiences of racism in the year before delivery had twofold higher odds of depression compared with those who did not (odds ratio 2.37, 95% CI 1.67-3.37) (21).…”
Section: Health Equitymentioning
confidence: 99%
See 1 more Smart Citation
“…Populations marginalized by racism and socioeconomic disadvantage experience significant health inequities in the prevalence, screening, treatment, and outcomes related to perinatal mental health conditions (7,102). Analysis of PRAMS (Pregnancy Risk Assessment Monitoring System) phase 8 2018 data, including 7,328 non-Hispanic Black respondents with live births from 11 states and New York City and controlling for potential confounders, showed that respondents who felt upset due to experiences of racism in the year before delivery had twofold higher odds of depression compared with those who did not (odds ratio 2.37, 95% CI 1.67-3.37) (21).…”
Section: Health Equitymentioning
confidence: 99%
“…Without an intervention in place, less than a quarter of individuals with detected depression in outpatient perinatal care settings will have any treatment, as defined by an initial mental health visit, never mind symptom resolution (20). In addition, although depression is more common, screening or treatment rates are lower for populations experiencing or marginalized by racism and socioeconomic inequities (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%